Gendered contributions in Bali’s lontar leaf craft industry: A study of women in Bona Village, Bali - Mahadewi, Ni Made Anggita Sastri; Niko, Nikodemus; Maheswari, I Dewa Ayu Agung Deanti; Nafisah, Lulu Kaisa (INTERNATIONAL JOURNAL OF CHILD AND GENDER STUDIES, 2026)
The palm leaf craft industry in Bona Village has flourished since the 1950s, coinciding with the popularity of Kecak dance performances. This qualitative research explores women’s involvement and gender-based roles in the industry. Observations and interviews with eight informants revealed a stark division of labor: men generally operate the machines, while women dominate the manual weaving techniques. Women’s roles are crucial at every stage. In the pre-production stage, they collect raw materials. During the production process, women are responsible for washing, cutting, dyeing, and shaping the palm leaves into finished products. In the distribution stage, they distribute their products to local collectors and art markets outside the village. Although not the primary source of income for most families, this industry holds significant economic and social value, contributing to the cultural identity of Bona Village. Balinese women in Bona Village not only fulfill reproductive and socio-religious functions but also play key roles in production, possessing economic sovereignty. These findings confirm the existence of a cultural meritocracy in which women serve as social shock absorbers in the face of crises. Theoretically, this research enriches contextual feminist studies on the relationship between Balinese culture, gender relations, and the household economy. Practically, this study provides recommendations for strengthening women's bargaining power in the traditional crafts industry and recognizing their complex role as drivers of the national economy in the postmodern era.